Effects of supplementation with a blend of trisodium citrate, creatine monohydrate, leucine, and blueberry extract on training-induced changes in leg extension strength, endurance, and muscle size - Trevor D. Roberts; Jocelyn E. Arnett; Dolores G. Ortega; Justin S. Pioske; Joseph F. Daugherty; Michael S. Tempesta; Alekha K. Dash; Richard J. Schmidt; Terry J. Housh (Journal of the International Society of Sports Nutrition)
Background This study examined the effects of 8 weeks of supplementation with a blend of trisodium citrate, creatine monohydrate, leucine, and blueberry extract (TCLB) during resistance training on leg extension (LegExt) strength, LegExt endurance, and quadriceps muscle size.Methods A randomized, double-blind design was used to compare the effects of TCLB to creatine monohydrate (CM) and placebo (PLA). Twenty-eight recreationally active men (mean ± SD: age = 20.6 ± 1.4 yr; body mass = 86.9 ± 11.6 kg) ingested either TCLB (n = 10), CM (n = 10), or PLA (n = 8) during 8 weeks of LegExt resistance training. The following assessments were conducted before and after the training: 1) LegExt 1-repetition maximum (1RM), 2) LegExt repetitions-to-failure at approximately 80% of pre-training 1RM, 3) cross-sectional area (CSA) values of the individual quadriceps muscles (rectus femoris [RF], vastus lateralis [VL], vastus intermedius [VI], and vastus medialis [VM]), and 4) the sum of the CSA values (CSAsum = RF + VL + VI + VM). Separate one-way ANCOVAs that were covaried for pre-training values were used to analyze differences in the adjusted post-training means, and dependent t-tests with Bonferroni corrections were used to assess post-hoc pairwise comparisons. Chi-squared tests were used to evaluate differences between groups in the proportion of subjects who exceeded the minimal important difference (MID = pooled SD × 0.5).Results The ANCOVAs indicated no significant (p = 0.110–0.542) group differences in the adjusted post-training means for LegExt 1RM, LegExt repetitions-to-failure, RF CSA, VL CSA, or VM CSA. The ANCOVAs for VI CSA (p = 0.002) and CSAsum (p = 0.006) were significant. Pairwise comparisons indicated that the TCLB group (VI CSA = 33.37 cm2; CSAsum = 99.09 cm2) exhibited greater (p = 0.001–0.005) adjusted post-training means for VI CSA and CSAsum than the PLA group (VI CSA = 31.64 cm2; CSAsum = 95.37 cm2). The Chi-square tests showed no significant (p = 0.136–0.867) differences in the proportion of subjects exceeding the MID for LegExt 1RM, LegExt repetitions-to-failure, RF CSA, and VM CSA across all group comparisons. The TCLB group (VI CSA = 40%; CSAsum = 60%) demonstrated a greater (p = 0.007–0.043) proportion of subjects exceeding the MID for VI CSA and CSAsum than the PLA group (VI CSA = 0%; CSAsum = 0%). The CM group (40%) exhibited a greater (p = 0.043) proportion of subjects exceeding the MID for VL CSA than the PLA group (0%).Conclusions Eight weeks of supplementation with a blend of TCLB during resistance training increased total quadriceps muscle size more than the PLA, primarily from enhanced increases in the size of the VI muscle, without affecting training-induced changes in LegExt strength and endurance.